Integrating Islamic Values in Teaching Grammar for Young Learners: A Guide for Educators - Nurfazri, Muhammad; Ruhullah, Mohammad Eisa; Marinda, Sri Mellia (Perhimpunan Intelektual Muslim Indonesia, 2024)
This study is intended to depict how impression learning (IL) principles were fused into an English class in an Indonesian Islamic elementary school and how the students' grammar skills were fostered during and after the learning process. This research implemented a classroom practice-based model to explore the delivery of IL programs, specifically focusing on teaching the preposition of places through the concept of singular and plural using simple present continuous tense to young learners. The IL principles were a combination of Talqiyyan Fikriyyan and inductive learning to make the teaching-learning process active, student-centered, and felt by pupils. A case study was also used to investigate various aspects of a particular phenomenon, including teaching steps, teacher-students dialogues, and student engagement in the learning process. Moreover, concrete materials were intentionally deliberated to stimulate students' senses, thus adding a unique dimension to the study. In addition, two intervention sessions were designed in which each intervention consisted of (a) teaching grammar from specific to general and (b) twelve steps of teaching IL principles (opening the class by giving a prayer, motivating and reminding the rules of learning, remembering the previous lesson, asking the students' prior knowledge related to the material and mentioning the lesson objective, stimulating students' interest in learning by observe and imitate, saying the sentences, installing the Islamic value, engaging students to play words card game, giving some rewards, question and answer, explaining the material comprehensively, and reflection). Hence, this study provides an alternative model of teaching grammar to young learners.